2002
DOI: 10.1618/jhes.5.87
|View full text |Cite
|
Sign up to set email alerts
|

Construct of Evaluation of Comprehensive Comfortableness in a Combined Environment of Audio-Visual Stimuli—The Relationship between Comprehensive Comfortableness and Harmonious Sensation

Abstract: This paper discussed the construct of evaluation in a combined environment of visual and auditory stimuli. In particular, we pointed out the relationship between a harmonious sensation of the two stimuli and comprehensive comfortableness. Ten subjects were asked to rate the image of twenty scenes on slides and sounds. In Experiment 1, they rated the individual image of each stimulus and in Experiment 2, they rated the combined image of the scene and sound.As a result of the experiments it became clear that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In the present study, we focused on the congruency between the environment and beverages. In research studies on psychological aspects of the architectural environment, experiments with combined (multisensory) environments have shown multisensory interactions in the evaluation of the environment (Gassho, Tamura, Matsubara, & Kurazumi, 2002; Matsubara et al, 2002; Matsubara, Gassho, & Kurazumi, 2004; Matsubara, Kawakami, Gassho, Kurazumi, & Yamato, 2005). In these studies, one of the important factors leading to multisensory interaction was the congruency between the environment and stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we focused on the congruency between the environment and beverages. In research studies on psychological aspects of the architectural environment, experiments with combined (multisensory) environments have shown multisensory interactions in the evaluation of the environment (Gassho, Tamura, Matsubara, & Kurazumi, 2002; Matsubara et al, 2002; Matsubara, Gassho, & Kurazumi, 2004; Matsubara, Kawakami, Gassho, Kurazumi, & Yamato, 2005). In these studies, one of the important factors leading to multisensory interaction was the congruency between the environment and stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a study conducted on the hue‐heat hypothesis, that is, that the thermal sensation is affected by a warm or cold color, the results revealed that the hue‐heat effect was facilitated when the participants evaluated the auditory environment, as well as the thermal environment (Matsubara et al, 2004). Comprehensive comfortableness in an environment can be improved by harmonizing the visual stimuli and auditory stimuli (Gassho et al, 2002). In an experiment in which the participants evaluated a landscape under various temperature and noise conditions, uncomfortable traffic sounds led to a decreased evaluation of the landscape (Matsubara et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Design of sound environment by intentionally adding some sounds was examined [1,2], and the comfortableness of some environments was evaluated by using the audio-visual stimuli based on the soundscape [3,4]. The former two studies [1,2] were carried out with various impression categories including comfortableness, but the effect of the conditions on additional sound was not statistically clear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the target environments were limited to public spaces. The latter two studies [3,4] aimed at evaluating the comfortableness of the sound environment using audiovisual stimuli recorded there, but no sound was added. There is a possibility of rather spoiling the comfortableness when the sound stimulus is added to the environment without considering the kind of its stimulus or sound level.…”
Section: Introductionmentioning
confidence: 99%